Effect of the mobility of ligands in polyrotaxanes on order structure of water clusters - Hirose, Hiroaki (Langmuir : the ACS journal of surfaces and colloids, 2004)
The effect of the mobility of ligands (maltose groups) in the polyrotaxanes (pRXs) on the structure of the surrounding water molecules was investigated. Raman spectra of collective OH stretching vibration of water molecules in aqueous solutions of maltose-pRX conjugates with different alpha-cyclodextrin (alpha-CD) threading on a poly(ethylene glycol) (PEG) chain was measured. The mobility of maltose groups was estimated by measuring the relaxation time T2 of the C1 protons in maltose groups bound on alpha-CD by NMR experiment. A positive correlation between the Raman intensity of the collective band and the relaxation time T2 was obtained. This result indicates that the degree of order of the water clusters is higher as the mobility of maltose groups increases in these conjugate solutions. It is suggested that rapid motion of maltose groups in the pRX conjugate can contribute to preserving ordered structure of the bulk water clusters